Characterization of Different Sources of Human MSCs Expanded in Serum-Free Conditions with Quantification of Chondrogenic Induction in 3D. (20th June 2019) - Fabre, Hugo; Ducret, Maxime; Degoul, Olivier; Rodriguez, Jonathan; Perrier-Groult, Emeline; Aubert-Foucher, Elisabeth; Pasdeloup, Marielle; Auxenfans, Céline; McGuckin, Colin; Forraz, Nico; Mallein-Gerin, Frédéric
Abstract : Mesenchymal stem cells (MSCs) represent alternative candidates to chondrocytes for cartilage engineering. However, it remains difficult to identify the ideal source of MSCs for cartilage repair since conditions supporting chondrogenic induction are diverse among published works. In this study, we characterized and evaluated the chondrogenic potential of MSCs from bone marrow (BM), Wharton's jelly (WJ), dental pulp (DP), and adipose tissue (AT) isolated and cultivated under serum-free conditions. BM-, WJ-, DP-, and AT-MSCs did not differ in terms of viability, clonogenicity, and proliferation. By an extensive polychromatic flow cytometry analysis, we found notable differences in markers of the osteochondrogenic lineage between the 4 MSC sources. We then evaluated their chondrogenic potential in a micromass culture model, and only BM-MSCs showed chondrogenic conversion. This chondrogenic differentiation was specifically ascertained by the production of procollagen IIB, the only type II collagen isoform synthesized by well-differentiated chondrocytes. As a pilot study toward cartilage engineering, we encapsulated BM-MSCs in hydrogel and developed an original method to evaluate their chondrogenic conversion by flow cytometry analysis, after release of the cells from the hydrogel. This allowed the simultaneous quantification of procollagen IIB and α 10, a subunit of a type II collagen receptor crucial for proper cartilage development. This work represents the first comparison of detailed immunophenotypic analysis and chondrogenic differentiation potential of human BM-, WJ-, DP-, and AT-MSCs performed under the same serum-free conditions, from their isolation to their induction. Our study, achieved in conditions compliant with clinical applications, highlights that BM-MSCs are good candidates for cartilage engineering.